High-temperature wettability and interactions between Hf-containing NbSi-based alloys and Y2O3 ceramics with various microstructures. (15th January 2018) - Wan, Beibei; Zhang, Huarui; Gao, Ming; Bai, Peng; Zhang, Hu
Abstract: To obtain improved mould shells with appropriate microstructures for directional solidification casting of NbSi-based alloys, Y2 O3 ceramics with various microstructures were designed and characterized. The mechanisms of high-temperature wettability and interactions between NbSi-based alloys and Y2 O3 ceramics were studied. The results showed that there was a characteristic transition in the wettability between the molten alloys and ceramics when the Y2 O3 microstructure changed. The spreading rate gradually decreased and the apparent equilibrium contact angle changed from 70.2° to 112.6° with the level of open porosity of Y2 O3 ceramics increasing from 3.6% to 27.2%. Wetting kinetics analyses indicated that the movement of the triple line during the wetting process was driven by the formation of continuous HfO2 reaction layer in the alloy-ceramic interface. The content of HfO2 particles inner the alloy matrix with the level of open porosity of Y2 O3 ceramics increasing from 3.6% to 27.2% initially gradually decreased and subsequently increased. Y2 O3 with open porosity level of about 20.7% were the most beneficial for directional solidification casting of high-purity Hf-containing NbSi-based alloys. Graphical abstract: Highlights: Mechanisms of high-temperature wettability and interactions between the molten NbSi alloys and Y2 O3 ceramic were clarified. Y2 O3 with open porosity level of about 20.7% was the most beneficial for DS casting of high-purity NbSi alloys. Wetting kinetics analyses indicated that the movement of triple line was driven by the formation of 1–5 μm HfO2 layer. The equilibrium contact angle changed from 70.2° to 112.6° with the porosity of Y2 O3 increasing from 3.6% to 27.2%.